Unyielding hope - Oke, Janette, 1935-; Logan, Laurel Oke (When hope calls, 2020)
"In the early twentieth century, Lillian Walsh rushes to a reunion after discovering the sister she believed dead is likely alive. But Grace has dreams beyond anything Lillian imagines. Can Lillian set aside her own plans and join her sister in an adventure that will surely change them both?"--